Faktor yang Berhubungan dengan Budaya Pemberian ASI Eksklusif di Puskesmas Makale Selatan Kabupaten Tana Toraja - Zadrak Tombeg; Erni Yetti R.; Anto J. Hadi; Saskiyanto Manggabarani (Jurnal Ners, 2023)
Tana Toraja Regency is experiencing cultural changes and modernization that can affect the practice of exclusive breastfeeding. Technological developments and outside cultural influences can cause shifts in traditional values ??and practices. The Tana Toraja culture has conflicting values ??related to the practice of exclusive breastfeeding. For example, traditional values ??that respect and prioritize family ties can go hand in hand with the practice of exclusive breastfeeding. However, other cultural factors such as customs involving supplementary feeding of infants may conflict with this practice. Cultural factors that involve the role of the family and society can be an obstacle in the practice of exclusive breastfeeding. This study aims to identify cultural factors that support exclusive breastfeeding. Type and design of a quantitative study using a cross-sectional study design conducted at the Makale Selatan Public Health Center, Tana Toraja Regency from May to June 2023. The population and sample were all 108 breastfeeding mothers with accidental sampling as the sample. The collection and processing of the data used were primary and secondary data using a questionnaire, as well as statistical analysis using the chi-square test and logistic regression. The results showed that the role of the elderly (p=0.017), the role of the family (p=0.001), religious and belief factors (p=0.014), traditions and cultural heritage (p=0.001) were related to the culture of exclusive breastfeeding, and the role of the elderly was the variable most related to Exp (B) = 12.320. The conclusion is that the role of the elderly, the role of the family, religious and belief factors and traditions and cultural heritage are factors that cause a culture of exclusive breastfeeding, so that programmed education efforts are needed regarding sustainable prenatal classes. By knowing these factors, appropriate strategies and interventions can be developed to promote the practice of exclusive breastfeeding in Tana Toraja District.